Outbreak of scabies among preschool children, Accra, Ghana, 2017 - Sackey, S.O.; Kaburi, B.B.; Ameme, D.K.; Adu-Asumah, G.; Dadzie, D.; Tender, E.K.; Addeh, S.V.; Aryee, T.; Addo-Lartey, A.; Wurapa, F.; Afari, E.A.; Kenu, E. (BMC Public Health, 2019)
Background: Scabies occurs worldwide with a prevalence between 0.3 and 46.0%. In Ghana, even though a 5.1% proportion of scabies was reported in a retrospective review of skin diseases at the Korle Bu Teaching Hospital, the nationwide prevalence of scabies is unknown. Overall, its burden is higher in tropical regions. Scabies outbreaks mostly occur among children, the elderly in nursing homes, and prison inmates. Even though primary scabies hardly results in mortalities, the pain, itch, and systemic complications from secondary bacterial infections account for about 1.5 million years lived with disabilities. We investigated a scabies outbreak among school children in Ghana to determine its magnitude, stop the outbreak, and institute preventive measures to minimize risks of future outbreaks. Methods: The investigation was conducted between March 14 and May 17, 2017 among pupils of Presbyterian Secondary Staff Basic School in Accra. We defined a case as a school child who on clinical examination, had an intensely pruritic rash on at least one typical predilection site with or without a burrow, or positive skin scrapings on microscopy. We screened and line listed cases, performed laboratory investigations on skin scrapings and wound swaps, and conducted an environmental assessment. We performed descriptive statistics on data, and calculated attack rate ratios (ARR) at 95% confidence level. Results: Of 823 preschool children screened, 92 were cases. Median age of cases was 4 years (range 2–7 years) and their modal age was 3 years. The overall attack rate was 11.2% (92/823). The sex specific attack rate was 11.5% for males, and 10.8% for females (ARR: 0.93; CI: 0.67–1.28). Compared with the least affected class (crèche), the nursery one class was worst affected (ARR: 5.14; CI: 3.44–7.50). On microscopy, all skin scrapings were negative for scabies. Staphylococcus aureus and Streptococcus spp. were isolated from secondarily infected scabies lesions. Conclusions: A scabies outbreak with a propagated source occurred among preschool children. The 3-year-old pupils were most affected. It was controlled by mass treatment with benzyl benzoate and health education. Classrooms and sleeping mats were disinfected. We recommended the decongestion of classrooms and discouraged sharing of sleeping mats.
Research Article
Keywords: Scabies; Outbreak investigation; Benzyl benzoate; Preschool children; Ghana